Exploring agroforestry systems and practices in the Terai and hill regions of Nepal - Ulak, S.; Lama, B.; Pradhan, D. K.; Bhattarai, S. (Banko Janakari, 2021)
This paper explores the status of agroforestry systems and practices in the Terai and hill regions of Nepal. Field survey, semi-structured interview and focus group discussions with the local farmers and stakeholders were conducted to explore the status of the agroforestry system and practices. The study covers forty-three districts, and represents agroforestry systems and practices in the Terai and hill regions of Nepal. Altogether, twelve agroforestry systems and forty-three agroforestry practices were documented in the Terai and hills of Nepal- ten systems in the Terai and seven systems in the hills. Agrisilviculture, agrisilvihorticulture, agrosilvopastoral, agrohortosilvopastoral, homegarden, hortiagriculture, silvofishery, agrosilvifishery, hortisilviculture and apiculture were the major agroforestry systems adopted in the Terai whereas those adopted in the hills included hortiagriculture, agrisilviculture, agrisilvihorticulture, agrosilvopastoral, homegarden, hortosilvipastoral and silvopastoral. The study revealed a gradual emerging scenario of commercial agroforestry systems in these regions although the continuation of traditional agroforestry systems was observed in most of the Terai and hill regions. Insufficient labour availability, fragmentation of land, market price fluctuation, lack of technical knowledge, and wild animal disturbances were some of the major challenges observed in the Terai and hills of Nepal.